Workload and response i̇n prehospi̇tal emergency health servi̇ces - Duran Metehan; Şahingöz Tahta Mehtap; Tahta Yahya (Halo 194)
Introduction/Objective In emergencies, it is crucial to avert preventable losses, get information as soon as possible, reach the scene quickly, and provide intervention by equipped and trained personnel. This study was conducted to analyse prehospital Emergency Health Services cases. Methods: This retrospective study examined 75.280 cases of people who called the Kayseri Emergency Health Services by dialling 112. The collected data include demographic characteristics, the reason for calling, the person who called, the arrival time, the diagnosis, the ambulance exit result, the names of hospitals where the cases were referred, etc., all collected on a form. Descriptive statistical methods were used for data analysis. Results: It was determined that the emergency calls were mostly made between 10 am and 4 pm, and 57.3% of the transfers were made to the Training and Research Hospital. Internal medicine problems were the main reason for calling. According to the ambulance exit results, 66.7% of the cases resulted in hospital transfers. Conclusions: The number of people calling emergency health services is increasing daily. Most callers were male, and the demand was highest during the daytime. More than half of the cases did not qualify as an emergency based on the international emergency parameters defined by the World Health Organization (WHO).